Association between ivermectin treatment and mortality in COVID-19: A hospital-based case-control study - Ravi Kirti; Alok Ranjan; Rajdeep Porel; Ketan Agarwal; Shaik M. Tahaseen; Shyama; Anjani Kumar (Journal of Family Medicine and Primary Care)
Purpose: This study was designed to test the hypothesis that exposure to ivermectin in early disease prevents mortality due to COVID-19. A secondary objective was to see if the drug has any impact on the length of hospital stay among the survivors. Methods: It was a hospital-based retrospective case-control study conducted at a tertiary teaching hospital in India. All patients with a diagnosis of COVID-19 who were admitted between 1st April and 15th May 2021 and received inpatient care were included. Important variables like demographic details, dates of admission and discharge or death, symptoms at the time of admission, comorbidities, severity of illness at the time of admission, whether ivermectin was administered or not during the course of the illness and other treatments received as part of the standard of care were retrieved from the medical records. Results: Of the 965 patients who received inpatient care, 307 died during their hospital stay while 658 were successfully discharged. The proportion of cases treated with ivermectin was 17.26% among the non-survivors (53/307) and 17.93% among the survivors (118/658). The effect was statistically insignificant (crude OR = 0.954; 95% CI: 0.668–1.364, P = 0.80). Among the survivors, the median length of stay was 11 days for patients who received ivermectin (IQR: 7–15) as well as for those who did not (IQR: 7–16). Conclusion: This study did not show any effect of ivermectin on in-patient mortality in patients with COVID-19 and there was no effect of the drug on the length of hospital stay among the survivors.